Effects of Social Network on Health Education (Shiksha Shastra Saurabh, 2018)
Social networks have become an inseparable part of our modern life. Social network, if used properly, can be very beneficial for all the users in every respect. There are many researched applications of Social network in different fields, its application in Health Education was not mentioned anywhere properly, though. For the survey, the students of Bachelors’ levels, majoring in Health and Physical Education in constituent and affiliated colleges of T.U. of Kathmandu Valley were selected from the different colleges. Altogether 171 students, who were acquainted with Social network, were selected as respondents for the study. Questionnaires were used to collect quantitative data and interview guidelines were used to obtain qualitative data from teachers.The students and teachers profoundly used Social network still they should use it for educational purpose. The communication gap between teachers and students were clearly perceived.